2014
DOI: 10.1016/s0959-8049(14)50278-x
|View full text |Cite
|
Sign up to set email alerts
|

312: Zoledronic acid impairs stromal reactivity by inhibiting M2-macrophages polarization and prostate cancer-associated fibroblasts

Abstract: Zoledronic acid (ZA) is a biphosphonate used for osteoporosis treatment and also proved to be effective to reduce the pain induced by bone metastases when used as adjuvant therapy in solid cancers. However, it has been recently proposed that ZA could have direct anti-tumour effects, although the molecular mechanism is unknown. We herein unravel a novel anti-tumour activity of ZA in prostate cancer (PCa), by targeting the pro-tumorigenic properties of both stromal and immune cells. Particularly, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Zoledronic acid (ZA) is an eligible agent of this kind, which has been FDA-approved as the third generation of amino-bisphosphonate agent for treating skeletal-related events (SREs) and pain caused by bone metastasis. Beyond the skeleton, plenty of studies have generated new insights into its potent role in modulating macrophages phenotypes [147]. According to those studies, ZA was able to reverse the polarity of TAMs from M2-like to M1-like by attenuating IL-10, VEGF, and MMP-9 production and recovering iNOS expression [99, 148].…”
Section: Potential Strategies Targeting Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoledronic acid (ZA) is an eligible agent of this kind, which has been FDA-approved as the third generation of amino-bisphosphonate agent for treating skeletal-related events (SREs) and pain caused by bone metastasis. Beyond the skeleton, plenty of studies have generated new insights into its potent role in modulating macrophages phenotypes [147]. According to those studies, ZA was able to reverse the polarity of TAMs from M2-like to M1-like by attenuating IL-10, VEGF, and MMP-9 production and recovering iNOS expression [99, 148].…”
Section: Potential Strategies Targeting Macrophagesmentioning
confidence: 99%
“…Based on this evidence, zoledronic acid has been added into the adjuvant endocrine therapy for premenopausal women with early-stage breast cancer in ABCSG-12 trial [125]. Data of 62 months’ follow-up [125] showed that the addition of ZA at clinically achievable doses delayed tumor recurrence and significantly prolonged disease-free survival, which provides a solid clinical evidence for ZA to be a promising agent for cancer prevention [147, 148]. Another agent capable of repolarizing TAMs to M1 phenotype is CP-870,893, which is an agonist monoclonal antibody (mAb) of CD40 [150, 151].…”
Section: Potential Strategies Targeting Macrophagesmentioning
confidence: 99%
“…Interestingly, this antibody was tested in a phase II trial (NCT00072930) for patients with metastatic prostate cancer in combination with standard-of-care docetaxel, prednisone, and zoledronic acid. Notably, steroids such as prednisone have been associated with inferior immunotherapy responses (11), whereas zoledronic acid can block the activity of M2 macrophages (12). Similarly, etaracizumab was tested in a phase II trial for melanoma in combination with the standard-of-care dacarbazine (13).…”
Section: Introductionmentioning
confidence: 99%